1990
DOI: 10.1159/000168048
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Nephrotoxicity in Humans and Experimental Animals

Abstract: Evidence from human case reports, epidemiologic studies and animal experiments have suggested that exposure to organic solvents is associated with a wide spectrum of renal disorders, including tubular necrosis, interstitial disease, glomerulonephritis and neoplasia. This review summarizes what is known about solvent-induced renal damage in humans and experimental animals, with emphasis on hypothesized mechanisms by which this broad range of disorders may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…These findings suggest that very high exposures, rather than prolonged low exposures, cause severe damage in the renal system. This finding is in accordance with those of studies (15)(16) associating acute tubular necrosis with high levels of exposure to organic solvents.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that very high exposures, rather than prolonged low exposures, cause severe damage in the renal system. This finding is in accordance with those of studies (15)(16) associating acute tubular necrosis with high levels of exposure to organic solvents.…”
Section: Discussionsupporting
confidence: 93%
“…Again, differences in the structure ofthe -56-kDa polypeptide subunit were noted. Work from several laboratories has subsequently revealed at least two isoforms for the vacuolar H+-ATPase -56-kDa subunit that are encoded by different genes (7)(8)(9). The present study examines how these isoforms might participate in the distinctive amplification and physiology of the vacuolar H+-ATPase observed in mammalian kidney.…”
mentioning
confidence: 92%
“…Previous case-control studies have primarily been conducted among patients with glomerulonephritis despite that most animal experiments have shown that solvent exposure leads to renal tubular damage (28,29). The only previous study of patients with CRF regardless of underlying disease (11) showed no more than a weak and statistically nonsignificant association with solvents overall.…”
Section: Discussionmentioning
confidence: 99%